First Trimester Initiation of Prenatal Care in the US-Mexico Border Region. Issue 8 (August 2015) - McDonald, Jill A.; Argotsinger, Brittany; Mojarro, Octavio; Rochat, Roger; Amatya, Anup
<x xml:space="preserve">Abstract</x> Objectives: To systematically examine prevalence of first trimester prenatal care (FTPNC) in the 44 US counties and 80 Mexican municipios of the binational border region; and to describe disparities between border and nonborder areas within states, border states, and countries. Methods: We combined 2009 records of singleton live births from the 10 US-Mexico border states (N=1, 370, 206) into a single file. We included FTPNC; county/municipio, state, and country of maternal residence; and demographic variables common to all records. We computed prevalence of FTPNC for border and nonborder residents by state and country. Using multivariable regression, we computed adjusted prevalence ratios (aPR) for FTPNC in border relative to nonborder residents, states relative to one another, and the US relative to Mexico. Results: In 2009, 68.8% of US-Mexico border mothers and 72.9% of nonborder mothers received FTPNC. After adjustment, nonborder residents had higher prevalence of FTPNC than border residents in Sonora, New Mexico, Arizona, Coahuila, and Chihuahua (aPR=1.09–124). In US states, prevalence was 13%–36% higher in New Mexico, Arizona, and California than Texas. In Mexico, when compared with Coahuila, adjusted prevalence was 12%–20% higher in neighboring states. Between countries, FTPNC prevalence in border counties/municipios was higher in Mexico among women with low parity/low education and in the United States among women with high parity/high education. Conclusions: In the US and Mexico, women in border counties/municipios receive less timely prenatal care than their nonborder counterparts, but the magnitude of the disparity varies by state. Lack of a consistent, binational approach to birth data collection requires cautious interpretation of findings.